2023
DOI: 10.3390/cancers15092622
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic-Related Proteins in Brain Gliomas: Role, Mechanisms, and Targeting Agents

Abstract: The present review focuses on the phenomenon of autophagy, a catabolic cellular process, which allows for the recycling of damaged organelles, macromolecules, and misfolded proteins. The different steps able to activate autophagy start with the formation of the autophagosome, mainly controlled by the action of several autophagy-related proteins. It is remarkable that autophagy may exert a double role as a tumour promoter and a tumour suppressor. Herein, we analyse the molecular mechanisms as well as the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 268 publications
(371 reference statements)
0
1
0
Order By: Relevance
“…Novel methods such as clustered regularly interspaced short palindromic repeats (CRISPRs)-CRISPR-associated protein (Cas9) genome editing and/or application of miRNAs and high-throughput technologies are underlined as key technologies to identify and understand autophagy targets in gliomas, in order to obtain additional information for the better treatment and management of therapy-resistant patients. Thus, it is suggested that this modern perspective could help in the selection of patients with gliomas that are most likely to respond to autophagy inhibition therapy, but also to identify patients resistant to treatment [6].…”
mentioning
confidence: 99%
“…Novel methods such as clustered regularly interspaced short palindromic repeats (CRISPRs)-CRISPR-associated protein (Cas9) genome editing and/or application of miRNAs and high-throughput technologies are underlined as key technologies to identify and understand autophagy targets in gliomas, in order to obtain additional information for the better treatment and management of therapy-resistant patients. Thus, it is suggested that this modern perspective could help in the selection of patients with gliomas that are most likely to respond to autophagy inhibition therapy, but also to identify patients resistant to treatment [6].…”
mentioning
confidence: 99%